2017
DOI: 10.1080/09546634.2017.1351608
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of cysteamine cream in the treatment of epidermal melasma, evaluating by Dermacatch as a new measurement method: a randomized double blind placebo controlled study

Abstract: Cysteamine cream showed significant efficacy in decreasing melanin content of the lesions, as established by Dermacatch as a new measuring method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 33 publications
4
97
0
3
Order By: Relevance
“…A double‐blind, randomized, vehicle‐controlled clinical study performed by Mansouri et al in 2015 on 50 melasma patients showed significant efficacy of cysteamine for the treatment of melasma . A second well‐controlled clinical trial also confirmed the efficacy of cysteamine for melasma treatment …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A double‐blind, randomized, vehicle‐controlled clinical study performed by Mansouri et al in 2015 on 50 melasma patients showed significant efficacy of cysteamine for the treatment of melasma . A second well‐controlled clinical trial also confirmed the efficacy of cysteamine for melasma treatment …”
Section: Discussionmentioning
confidence: 90%
“…Body cells produce cysteamine through the conversion of coenzyme A to pantethine which is then broken to cysteamine. 6 The depigmenting action of cysteamine has been shown by Chavin et al 7,8 and Frank et al 9 Their findings were indicative of a more potent depigmenting affect for cysteamine com- Considering the results of the two well-controlled clinical studies that confirm its efficacy in the treatment of melasma 13,14 and its high safety profile, cysteamine might replace mutagenic and potentially hazardous depigmenting agents in future.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of other trials revealed a mean 38-58% decrease in mMASI scores promoted by topical cysteamine after 120 days, which is consistent with our results. 12,13,23 Moreover, the assessment after 240 days of topical cysteamine disclosed an additional 18% mMASI reduction. 12 A substantial variability was evident in the mMASI and colorimetric reduction for both groups, leading to the hypothesis that other variables interfered with the performance of the treatments.…”
Section: Discussionmentioning
confidence: 92%
“…A recent change in the formulation of cysteamine led to the reduction in the sulfur odor and skin irritability, allowing its use as a cream that has proven to be effective in the topical treatment of melasma. [11][12][13] However, to date no study has compared this formulation of topical cysteamine to 4% hydroquinone in the treatment of melasma.…”
Section: Introductionmentioning
confidence: 99%